Development of Integrated Curriculum-Based Mathematics Teaching Materials to Effectively Teach 21st Century Capabilities: Draft 1 Teaching Material Design - Rusmini Rusmini; Fitrah Sari Wahyuni Harahap (Jurnal Scientia, 2022)
The purpose of this research is to produce valid, effective, and practical textbooks. In the short term, it aims to produce valid and practical teaching materials for linear algebra courses. Validity based on the relevance of the expected competencies i.e. 21st century competencies. Practicality is measured by the use of teaching materials in classroom learning. This study used a development research design, followed by four steps: 1) initial research, 2) prototyping, 3) summative evaluation, 4) reflection and documentation. In our initial research, we analyzed the need for teaching materials for the Information Systems study program, the reason being that students really needed linear algebra teaching materials that had applied concepts that were described visually that were easy to understand by students. In the prototyping stage, we write teaching materials according to the needs analysis. The prototype was discussed with experts, revised after summative evaluation and implemented during lecture meetings. The result is the final product in the form of teaching materials used during reflection. Our systemic documentation was written according to the established research framework. Finally, a valid, practical linear algebra teaching material has been produced